Environmental aspects of the agreement between the European Union and Mercosur (Research, Society and Development, 2021)
After 20 years of diplomatic derivation, it was signed as the basis for the economic integration agreement between the Common Market of the South (Mercosur) and the European Union (EU). On June 28, 2019, negotiations were concluded in Brussels on an Association Agreement that provides for the establishment of a free trade zone comprising the two blocs. Among the 17 chapters of the free trade agreement, there is the chapter “Trade and Sustainable Development” in which it is pre-agreed that the member countries of the two blocs must reiterate multilateral commitments signed, such as those of the United Nations Framework Convention on the Change of Climate and the Paris Agreement. In addition, other efforts related to the conservation and sustainable use of biodiversity, respect for labor rights and protection of the rights of indigenous populations would be added. This article aims to present the environmental policies provided for in this agreement. As a research method, a bibliographic survey on academic research sites was used, in addition to reports in large-circulation newspapers. First, a brief history of the negotiation regarding environmental policies will be made. Once removed, a normative legal analysis of the text of the agreement is carried out, specifically with regard to the chapter on sustainable development, in free translation of the original text. Finally, a brief conclusion about the obstacles to the effectiveness of this agreement to the environmental policies it causes, used by the Ministry of the Environment, of the Federal Government since 2020, after the publication of the draft.